2012
DOI: 10.4103/0019-5413.104241
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar dislocation of the clavicle

Abstract: Bipolar dislocation of the clavicle at acromioclavicular and sternoclavicular joint is an uncommon traumatic injury. The conservative treatments adopted in the past is associated with redislocation dysfunction and deformity. A 41 years old lady with bipolar dislocation of right shoulder is treated surgically by open reduction and internal fixation by oblique T-plate at sternoclavicular joint and Kirschner wire stabilization at acromioclavicular joint. The patient showed satisfactory recovery with full range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Castropil et al reported successful outcomes with semitendinosus allografts for treatment of isolated SCJ dislocations [ 20 ]. Tendon allografts may be a favorable alternative to metal hardware, such as K-wires since there have been several reports of cardiac tamponade and tracheoinnominate artery fistula resulting from the migration of K-wires [ 14 , 21 , 22 ]. Also, a tendon allograft reliably provides flexibility and stability for the treatment of these difficult injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Castropil et al reported successful outcomes with semitendinosus allografts for treatment of isolated SCJ dislocations [ 20 ]. Tendon allografts may be a favorable alternative to metal hardware, such as K-wires since there have been several reports of cardiac tamponade and tracheoinnominate artery fistula resulting from the migration of K-wires [ 14 , 21 , 22 ]. Also, a tendon allograft reliably provides flexibility and stability for the treatment of these difficult injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors implemented various procedures for SCJ augmentation to prevent further recurrence or instability. The techniques they used included fixation with metal devices such as a Kirschner wire [ 11 , 20 , 21 ], cerclage wire [ 13 ], compression screw [ 1 ], T-plate [ 12 ], and hook plate [ 22 ], as well as ligamentous reconstruction with polyester fiber tape [ 4 ], polyester surgical mesh [ 7 ], muscle strip [ 36 ], and tendon graft [ 23 ]. Most of these devices were sufficient to prevent recurrence, but the SCJ has an ROM of a maximum of 40°, and rigid joint bridging fixation may compromise shoulder movement.…”
Section: Discussionmentioning
confidence: 99%